Pengaruh Pass And Move Training terhadap Peningkatan Kemampuan Passing dan Control Atlet Sepak Bola U-15 di Akademi R19 Kendal Tahun 2022 - Riswanto, Adi; Sudarmono, Martin (Universitas Negeri Semarang, 2023)
The aim of the study was to determine the effect of pass and move training on improving the passing and control abilities of U-15 football athletes at the Kendal R19 Academy. The research method uses experimental research with a population and sample of 20 athletes. The results of the first hypothesis research obtained were 19.304 > t table 2.093 with a percentage increase of 33% so that there was an increase in passing ability in the U-15 football athlete at the Kendal Academy of R19. The second hypothesis is that the t value is 9.037 > t table 2.093 with a percentage increase of 28% so that there is an increase in the ability to control the U-15 football athletes at the Kendal Academy of R19. In conclusion, there is an effect of pass and move training on passing ability in U-15 soccer athletes at Kendal R19 Academy. There is also the effect of pass and move training on the control ability of U-15 soccer athletes at the Kendal R19 Academy. So that pass and move training can be a training reference that can improve the athlete's passing and control abilities.